HOW "PATIENT CHOICE" AFFECTS HOSPITAL RECOMMENDATIONS OF SKILLED NURSING FACILITIES. (11th November 2018) - Tyler, D; Gadbois, E A; McHugh, J P; Shield, R R; Winblad, U; Mor, V
Abstract: To better understand how patients choose SNFs, we interviewed 138 staff from 16 hospitals and 25 SNFs in eight cities in the US, and in five cities, 98 patients who had recently been admitted to participating SNFs. Interviews were qualitatively analyzed for underlying themes. Consistent with what we heard from hospital staff, most patients described receiving lists of SNFs from hospital staff but no guidance to aid their choice of SNFs. Staff reported not sharing quality data with patients because they believed that patient choice requirements precluded their doing so. Though patients were only given facility addresses, and selected the SNF nearest their home, most patients said they would have traveled farther if a better SNF had been recommended. Strict interpretations of patient choice requirements may thus prevent how quality data about SNFs are shared. Patients' choices may, therefore, preferentially focus on geography rather than on readily available quality data.